Prevalence of high-risk human papillomavirus types 16 and 18 in healthy women with cytologically negative pap smear in Iran - Safaei Akbar; Khanlari Mahsa; Momtahen Moghdeh; Monabati Ahmad; Robati Minoo; Amooei Sedigheh; Valibeigi Behnaz; Azarpira Negar (Indian Journal of Pathology and Microbiology, 2010)
Background: Because human papillomavirus (HPV) is one of the causal factors in cervical cancer, understanding the epidemiology of this infection is an important step towards developing strategies for prevention. Materials and Methods: We evaluated the prevalence of high-risk human papillomavirus Types 16 and 18 in cervical samples from 402 healthy women with normal Pap smears by testing with type-specific primers in the polymerase chain reaction. Participants were seen at two gynecological clinics affiliated to the Shiraz University of Medical Sciences in Iran. Result: The prevalence of positive HPV findings was 5.5%; high-risk HPV human papillomavirus Type 16 prevalence was 2% and no patient harbored HPV-18. The prevalence of HPV was 4.5% in younger age group and gradually increased to 20% in the 4 th decade. Conclusion: The prevalence of high-risk HPV was highest in the youngest women and gradually decreased with age. Overall, the prevalence of HPV in our population is low.